SISTEM INFORMASI INVENTORY CONTROL MINUMAN CAP BADAK MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA PT. JASA HARAPAN BARAT - Elma Fiana; Charles Jhony Mantho Sianturi; Erwin Ginting (Jurnal Inovasi Penelitian, 2021)
Jasa Harapan Barat is a company unit engaged in the marketing and distribution division of Badak stamp soft drinks located in Tanjung Morawa Km 7.5 Medan. During this time, PT. West Hope Services in processing the inventory data is still done manually, such as recording incoming goods and releasing goods recorded in the ledger in accordance with receipts or travel documents from customers or suppliers that contain how many items are purchased and sold. Then just copied back into Microsoft Excel by the office, so that sometimes have difficulty in calculating the stock of goods and to get inventory information does not match the availability of goods in the warehouse. So that the delivery of inventory information is less effective. To overcome these problems, we need a web-based inventory control information system so that the control of Badak stamp beverage inventory at PT. Jasa Harapan Barat can run effectively and efficiently. This research applies the Economic Order Quantity (EOQ) method to control inventory of goods so that there is no shortage or over ordering. The purpose of making this system is to make it easier to control the rhino stamp beverage inventory so that the resulting report is also more accurate.